The Influence of Pressure Level on the Behavioral Risk Level of Correctional Inmates: Pengaruh Tingkat Tekanan Terhadap Tingkat Resiko Perilaku Menyimpang Warga Binaan Pemasyarakatan - Dhika, Rangga Wahyu (Psikologia : Jurnal Psikologi, 2020)
The results of mental health disorders research by the University of South Wales showed that 36% experienced mental health disorders in the form of anxiety and women, the incidence rate was higher than men, 61%: 39%. The study was conducted 62 surveys in 12 countries covering 22,790 correctional prison residents found that every 6 months there was a prevalence of psychosis in men 3.7% and women 4% major depression in men 10% and women 12% and personality disorders in men 65% men and 42% women. From these data, many Penitentiary Citizens experience mental health disorders such as stress and sexual deviations. Deviations committed by Penitentiary Members include such as hallucinating / fantasizing, masturbating, and biological violation activities carried out by men and women in Correctional Institutions. This study uses the General Strain Theory theory by Robert Agnew using a quantitative approach. The data collected uses primary data in the form of distributing questionnaires to a predetermined sample of Penitentiary Guards. From the results of the study above the level of risk of deviant behavior of Correctional Guidance Citizens continues to increase along with the increasing level of pressure experienced by Correctional Guidance Citizens